Tuskegee airmen [ - Stentiford, Barry M. (Landmarks of the American mosaic, 2012)
The 'Tuskegee Airmen' - the first African American pilots to serve in the US military - were comprised of the 99th Fighter Squadron, the 332nd Fighter Group, and the 477th Bombardment Group. This title depicts the Tuskegee Airmen at the junction of two historical trends